Validity Parameters of the Human Papillomavirus Detection Test Hybrid Capture 2 With and Without Cytology After Laser Destruction and Large Loop Excision of the Transformation Zone Treatment of High-Grade Cervical Intraepithelial Neoplasia Lesions. Issue 4 (October 2017) - Hansen, Johanna; Waibel, Julia; Timme, Sylvia; Gitsch, Gerald; Bossart, Michaela; Oehler, Martin K.; Klar, Maximilian
Abstract : Objective: The aim of this study was to calculate the validity parameters of the Digene Hybrid Capture 2 (HC2) high-risk human papillomavirus DNA test with and without cytology in the follow-up examinations after laser treatment of the transformation zone or large loop excision of the transformation zone (LLETZ) for cervical intraepithelial neoplasia (CIN). Methods: We performed a standardized follow-up examination in 113 postlaser and 153 post-LLETZ patients in our colposcopy clinic. Routine cytology, HC2 tests, and colposcopically-guided cervical biopsies were performed and sensitivity, specificity, and positive and negative predictive values were calculated using the histological cervical biopsy result as the criterion standard. Results: After a median follow-up time of 25.5 months, the overall posttreatment recurrence/persistence rate of CIN 2 or higher (CIN 2+) was 24% after laser and 12.4% after Post-LLETZ treatment. Hybrid Capture 2 alone had a sensitivity/NPV of 70/88% in post-laser and 70/93% in post-LLETZ patients. Cytology alone had a sensitivity/NPV for CIN 2+ of 48/84% in post-laser and 58/91% in post-LLETZ patients. Combined testing of HC2 with cytology had a sensitivity/NPV of 81/92% in postlaser and 88/95% in post-LLETZ patients. Discussion: In this test of cure study, combined testing of cytology with HC2 resulted in a high sensitivity and NPV. Hybrid Capture 2 and cytology-negative women may safely return to routine recall. Cytology alone is not an adequate follow-up strategy in postlaser patients. Abstract : Hybrid capture 2 in combination with cytology leads to the best sensitivity and negative 31 predictive values after CIN treatment with laser or large loop excision of the transformation zone. Supplemental digital content is available in the text.